Dampak “Positif” Covid 19 terhadap Peningkatan Ekonomi Warga di Perumnas Tebak Rapak Melalui Usaha Rumahan - edwarman, edwarman; Putra, Muhamammad Bima Eka (Jurnal Adminitrasi Bisnis Nusantara, 2022)
The purpose of this study is to determine the positive impact of covid 19 on improving the economy of the community, especially in Tebak Rapak housing estate. Many obstacles are quite heavy and for a long time that all humanity has to overcome, which is the Covid19 pandemic.. The first information about the emergence of this pandemic came from China. According to the Chinese government, the origin of the virus that causes Covid19 came from a wet market selling animals commonly eaten by Chinese people such as mice, bats, etc. (Handayani, 2020: 120). Ultimately, this virus spreads and kills human souls, social systems, economies and others. This study uses descriptive method with qualitative approach to obtain data and information. The researchers will try to analyze data obtained from multiple sources to see how the community's economy has performed during the pandemic, especially in terms of the impact that communities, especially residents residents of the Tebak Rapak complex feel. The researchers used four techniques to analyze the data, namely observation, interview, document, and then the data from observations, interviews and documents will be triangulated. The result of this study is that facing article 19, the community can gain positive impacts: 1) from the economic sector where housewives achieve economic improvement: through activities Promising home businesses are businesses that can be run from home without the need to work outside. 2) You do not need to have a large capital, nor do you need to rent a store, you can sell because this can be your home business. 3) You don't need to meet many people in person, so you can still use government-recommended health care protocols, reducing the spread of the COVID19 virus